Growth in a time of change : global and country perspectives on a new agenda - Kim, Hyŏn-uk; Qureshi, Zia, 1953- (Brookings Institution Press, 2020)
"Addresses new issues and challenges for economic growth arising from ongoing significant change in the world economy, focusing especially on technological transformation. Analyzes how technological change, shifts in investment, and demographic transition are affecting potential economic growth globally and across major groups of economies. The contributors explore possible scenarios for the global economy as the digital revolution drives rapid technological change, including impacts on growth, jobs, income distribution, trade balances, and capital flows. Technology is changing the global configuration of comparative advantage and globalization increasingly has a digital dimension. The implications of these developments for the future of sectors such as manufacturing and for international trade are assessed. Part II of the book addresses new issues in the growth agenda from the perspective of an individual major economy: South Korea. The chapters in this section analyze how macroeconomic developments and technological change are influencing the behavior of households and firms in terms of their decisions to consume, save, and invest. Rising income and wealth inequalities are a major concern globally. Against this backdrop, trends in the labor income share and wage inequalities in South Korea are analyzed in terms of the role played by technology, industrial concentration, shifts in labor demand and supply, and other factors. Throughout the book, the contributors, in their analysis of both global and Korea-specific trends and prospects, place emphasis on drawing implications for policy"--